TYPICAL BEHAVIOUR OF JUVENILE DELINQUENCY IN SENIOR HIGH SCHOOL STUDENT - Yustisi Maharani Syahadat (JURNAL KESEHATAN MERCUSUAR, 2019)
This study aims to see how the typical behavior of juvenile delinquency is carried out by high school students. This research uses a qualitative approach. Taking participants in this study using purposive sampling techniques with the characteristics of participants is a teenage student in high school who lived separately from his parents since the beginning of high school with a research location in one private school. Researchers also use key person techniques, where researchers get complaints from several teachers from the school. The number of clients in this study was 1 person. Data collection techniques with semi-structured interviews, semi-participant observation and data analysis were performed using thematic analysis. This study revealed the typical symptoms/ behavior of juvenile delinquency displayed by the client. The negative behavior of these participants raises problems in the field of education and relationships with family and social environment.